Research of the Problem of Autism and Autistic Disorders: Theoretical Aspect - Bazyma, Nataliia; Lyndina, Yevheniia; Rasskazova, Olha; Kavylina, Ganna; Litovchenko, Olha; Hrynyk, Iryna (My University, 2022)
The causes of autism remain insufficiently differentiated. It is unlikely that any single disorder can be considered as the only cause of various symptoms and severity of autistic disorders. Although the specific causes of autism remain unclear, significant progress has been made in understanding the possible mechanisms of the disease. Turning to historical sources, we find that the origin and origin of the term «autism» are associated with forming a system of knowledge on the problem of diagnosis and further therapeutic work with children who need unique approaches to learn and educate. Analysis of the classifications of autism reveals the ambiguity of approaches to them. The first attempts at differentiation in the middle of childhood autism syndrome were clinical classifications based on the syndrome’s etiology. They play a significant role in developing adequate approaches to providing medical care to children with autism. Psychological and pedagogical tasks required other approaches to determine, depending on the specific situation, the specialization, strategy, and tactics of correctional work. First of all, there was a search for prognostic signs that would assess the possibilities of mental and social development of children in this category. To this end, some scholars have put forward criteria for assessing speech and intellectual development. The analysis of difficulties of the unanimous possibility of classification on separate indicators of mental development of the child (intelligence, speech, behavior, self-regulation, etc.) can be explained by parallel existence of classifications operating today in world practice.
Research of the Problem of Autism and Autistic Disorders: Theoretical Aspect / Nataliia Bazyma, Yevheniia Lyndina, Olha Rasskazova, Ganna Kavylina, Olga Litovchenko, Iryna Hrynyk // Revista Romaneasca Pentru Educatie Multidimensionala, 2022. – Vol. 14. – Issue 2. – P. 301–317
Keywords: механізми захворювання, інтелектуальний розвиток, терапевтична робота з дітьми, клінічна класифікація, етіологія синдрому, корекційна робота, соціальний розвиток дітей; mechanisms of disease, intellectual development, therapeutic work with children, clinical classifications, etiology of the syndrome, correctional work, social development of children